STUDI KONVERGENSI MESH PADA RESPONS HANCUR NUMERIK STRUKTUR SANDWICH HONEYCOMB - Syahiir Kamil; M. Nizar Machmud; Iskandar Hasanuddin; Faris Ahmad Mizanus Sabri; Taufan Arif Adlie; Zainal Arif (Badan Penerbit Universitas Muria Kudus, 2026)
In this research, finite element methods are utilized to investigate the mechanical behavior of aluminium honeycomb sandwich structures under out-of-plane compression. The structures were virtually compressed from the initial elastic regime until the plateau phase using explicit non-linear analysis modelling approaches. A mesh convergence study is conducted to ensure the accuracy and reliability of the simulation results, aiming to determine the optimal mesh size that balances precision with computational efficiency. An analytical equation for calculating the plateau force, or average crush load, along with experimental data from the study by Mertani, is used to validate the numerical results. The study concludes that a mesh size of 0.5 mm offers an ideal balance between accuracy and computational cost, yielding an error of 3.1%.